2009
DOI: 10.1016/j.febslet.2009.03.033
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 2‐deoxy‐d‐glucose on Werner syndrome RecQ helicase gene

Abstract: Caloric restriction (CR) is known to effectively elongate mammalian life-spans. The compound 2-deoxy-D-glucose (2DG), which is often used as an inhibitor of glucose utilization, is a mimetic agent of CR. In this study, we examined the changes of telomerase and Werner's syndrome RecQ (WRN) helicase after treatment with 2DG, because of the involvement of recQ helicase in the regulation of telomeres. Interestingly, 2DG treatment increased the expression of WRN protein in accordance with induction of its promoter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 29 publications
2
49
0
Order By: Relevance
“…Suppressing the formation of the free radical scavenger-reduced glutathione using 2-deoxy-glucose (2-DG) causes the up-regulation of WRN expression. 42 This event is consistent with the observation that fibroblasts derived from patients with WS are resistant to hydrogen peroxide induced cell cycle arrest. 43 Moreover, pre-clinical studies have shown the anti-tumor efficacy of 2-DG in combination with 5-fluorouracil, and ionizing radiation in pancreatic cancer.…”
Section: Conclusion and Prospectivesupporting
confidence: 91%
“…Suppressing the formation of the free radical scavenger-reduced glutathione using 2-deoxy-glucose (2-DG) causes the up-regulation of WRN expression. 42 This event is consistent with the observation that fibroblasts derived from patients with WS are resistant to hydrogen peroxide induced cell cycle arrest. 43 Moreover, pre-clinical studies have shown the anti-tumor efficacy of 2-DG in combination with 5-fluorouracil, and ionizing radiation in pancreatic cancer.…”
Section: Conclusion and Prospectivesupporting
confidence: 91%
“…2DG and Rsv, which are known as a potent inhibitors of glucose metabolism [109], and an activator of sirtuin-mediated de-acetylation [111], respectively, are often referred as CR mimetic drugs. We observed moderate activation of telomerase activity in HeLa S3 cells with 2DG and Rsv treatment [110,112], suggesting that CR mimetic drugs have protective effects on telomeres by inducing telomerase activity along with up-regulating expression of the telomere maintenance factor-encoding genes.…”
Section: Effect Of Caloric Restriction (Cr) Mimetic Drugs On Telomerementioning
confidence: 99%
“…Our previous studies demonstrated that caloric restriction (CR) mimetic compounds, such as 2-deoxy-D-glucose (2DG) and transresveratrol (Rsv) moderately enhance telomerase activity along with induction of WRN gene expression in HeLa S3 cells [17,18]. Luciferasereporter transfection experiments showed that these CR mimetic compounds up-regulate relative promoter activities of the 5'-upstream regions of human telomere-associated proteins and shelterin-encoding genes when compared with that of the PIF1 gene [19].…”
Section: Methodsmentioning
confidence: 99%